2014
DOI: 10.1021/ed400592w
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Program for Mentoring Students in a Two-Year Chemical Technology Program by an Alumnus Enrolled in Graduate School

Abstract: Implementation of a program for mentoring students in a two-year chemical technology program by an alumnus enrolled in graduate school is described. The graduate student provided tutoring and was also available to discuss advisement, opportunities for higher education, and career options. In turn, the organic chemistry professor mentored the graduate student in order to cultivate the graduate student's skills mentoring undergraduates, provide support for graduate degree completion, and promote professional dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Mentorship is especially crucial for first-year students who are making a challenging transition from high school studies and can potentially come from graduate students, faculty members, and upper-year undergraduates. One chemistry initiative involved graduate students providing office hours for undergraduates, with an increase in course passing grades observed after implementation . Faculty mentorship and recruitment advisor assistance were also significant for student success and retention within science, technology, engineering, and mathematics (STEM) programs. Support from upper-year students improved chemistry grades of first-year undergraduates across different institutions, , and a study by Arrington and colleagues indicated that senior mentors piqued student interest in collaborative laboratory work .…”
mentioning
confidence: 99%
“…Mentorship is especially crucial for first-year students who are making a challenging transition from high school studies and can potentially come from graduate students, faculty members, and upper-year undergraduates. One chemistry initiative involved graduate students providing office hours for undergraduates, with an increase in course passing grades observed after implementation . Faculty mentorship and recruitment advisor assistance were also significant for student success and retention within science, technology, engineering, and mathematics (STEM) programs. Support from upper-year students improved chemistry grades of first-year undergraduates across different institutions, , and a study by Arrington and colleagues indicated that senior mentors piqued student interest in collaborative laboratory work .…”
mentioning
confidence: 99%